1984
DOI: 10.1128/aac.25.6.719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of halothane on the replication of animal viruses

Abstract: Five RNA-and two DNA-containing viruses were propagated in Vero cells and tested for their ability to replicate in the presence of halothane (2-bromo-2-chloro-1,1,1-trifluoroethane), a commonly used inhalational anesthetic. Halothane did not affect poliovirus replication at any anesthetic concentration tested, but all other viruses were either partially or totally inhibited by clinical doses of the anesthetic. Replication of Sendai virus, simian virus 40, vesicular stomatitis virus, and herpes simplex virus ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
8
1
1
Order By: Relevance
“…It has been reported that volatile general anesthetics possess antiviral activities, probably by blocking viral RNA synthesis (15,16). For example, halothane differentially inhibits the replication of a number of RNA-and DNA-containing viruses (4,5). In contrast, in the present study, the general anesthetic chloral hydrate had no effect on rabies virus synthesis; however, the lack of an antiviral effect with chloral hydrate could be due to the fact that it is clinically less potent than ketamine.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been reported that volatile general anesthetics possess antiviral activities, probably by blocking viral RNA synthesis (15,16). For example, halothane differentially inhibits the replication of a number of RNA-and DNA-containing viruses (4,5). In contrast, in the present study, the general anesthetic chloral hydrate had no effect on rabies virus synthesis; however, the lack of an antiviral effect with chloral hydrate could be due to the fact that it is clinically less potent than ketamine.…”
Section: Discussioncontrasting
confidence: 54%
“…Clinically, halothane (2-bromo-2-chloro-1,1,1-trifluoroethane) anesthesia appears to beneficially alter the course of upper respiratory tract infections in children (13). Halothane at least partially inhibits the replication of most animal viruses in Vero cells as well (3). In order to gain insight into this mechanism, we have been studying the molecular events which occur in measles virus-infected cells which have been exposed to this widely used volatile anesthetic.…”
mentioning
confidence: 99%
“…After the third round of plaque purification, the resulting virus was passaged twice more as described above, and high-titer MVr stocks (1 x 107 to 4 x 107 PFU/ml) were made. Infectious measles virus was assayed by the plaque assay procedure described previously (3). Vero cells were exposed to halothane with a Drager vaporizer as described previously (8).…”
mentioning
confidence: 99%
“…The graph shows depressed influenza A virus titers in halothane-exposed animals at 12 h. *p<0.05. results obtained from mice given higher in fectious dosages of the virus. At the higher virus inoculum, there was an increased mor tality (up to 90%) which generally occurred at an earlier time after infection (days [5][6]. The mortality in these mice was greater in the control group than in the group receiving halothane anesthesia (data not shown).…”
Section: Effect O F the Anesthetic Agent On A Pulmonary Influenza A Vmentioning
confidence: 87%
“…One possible explanation may involve inhi bition of viral replication. Indeed, halothane, enflurane, and isoflurane have been shown to inhibit the replication of several classes of virus in vitro [5,6]. It is difficult to propose that anesthetic inhibition of viral replication is the only mechanism of decreased viral pathogenesis following exposure to volatile anesthetics, as this inhibition is quickly re versed following removal of the anesthetic agent.…”
Section: Introductionmentioning
confidence: 98%